BALANCED SCORECARD NA GESTÃO UNIVERSITÁRIA: MAPEAMENTO SOBRE O TEMA UTILIZANDO O PROKNOW-C - Lucas dos Santos Matos (Universidade Federal de Santa Catarina, 2015)
The growing importance of higher education in economic and social scenario has forced universities to improve their management methods, and one of the forms used has been the application of the Balanced Scorecard. This research, exploratory and descriptive in nature, with qualitative and quantitative, objective to build the necessary knowledge about the u se of the Balanced Scorecard in university management, performing a mapping on the topic from the boundaries of the researchers. This knowledge is made tangible by the selection of relevant articles and with scientific recognition on the topic. It is used bibliometric analysis of international literature, through the process Knowledge Development Process - Constructivist (ProKnow - C). The main results were: (i) International Journal of Educational Management is the period of greatest prominence; (ii) "Commod ification of education and academic LABOUR - using the balanced scorecard in a university setting" stands out among the articles; (iii) Janne Kettunen is the most prolific author.